Address By Y .B . Enche Tan Phock Kin ,State Executive Councillor at The Annual Dinner And Dance Of The Penang Sports Club at the Club Premises on Saturday 15th May 1971 at 8.00 pm - Enche Tan, Phock Kin

(untitled)
I wish first of all to convey the apologies of the Hon ' ble the Chief Minister for his inability to attend this function tonight due to urgent State business .